The Market for liars: Reputation and auditor honesty - Andrew McLennan; In-Uck Park (Osaka University, Institute of Social and Economic Research (ISER), 2003)
In the model there are two types of financial auditors with identical technology, one of which is endowed with a prior reputation for honesty. We characterize conditions under which there exists a 'two-tier equilibrium' in which 'reputable' auditors refuse bribes offered by clients for fear of losing reputation, while 'disreputable' auditors accept bribes because even persistent refusal does not create a good reputation. The main findings are: (a) honest auditors charge higher fees, and have economic profits accruing to reputation; (b) as the fraction of auditors who are honest increases, the premium charged by reputable auditors eventually decreases, which diminishes the incentive to refuse bribes; (c) if the fraction of honest auditors exceeds an upper bound, there does not exist a two-tier equilibrium; (d) thus the reputation mechanism may be undermined by entry into the honest segment of the industry, if it is possible; (e) increasing auditor independence increases the upper bound.
Keywords: M41; D82; G14; 330; auditing; reputation; adverse selection; auditor independence; Wirtschaftsprüfung; Adverse Selektion; Reputation; Theorie